ANALISIS KAUSALITAS TINGKAT SUKU BUNGA, INFLASI, NILAI TUKAR RUPIAH DAN INDEKS HARGA SAHAM GABUNGAN DI INDONESIA - Awan, Nur; Yudiantoro, Deny (Berajah Journal, 2025)
This study is motivated by the importance of macroeconomic variables in stock market investments, such as interest rates, inflation, and exchange rates. The Composite Stock Price Index (IHSG) is often used as an indicator of Indonesia's capital market development, providing a general market overview. IHSG movements are significantly influenced by macroeconomic conditions, making it essential to analyze these variables to minimize investment risks. This research employs a quantitative approach with an associative type of study. Data were collected from the official websites of the Indonesia Stock Exchange and Bank Indonesia using purposive sampling, with a total of 60 samples. The analysis utilizes time series data and includes tests such as unit root test, optimum lag, stability, Granger causality, cointegration, VECM, IRF, and VD, processed with E-Views 9 software. The results show: 1) A unidirectional causality relationship exists between IHSG and the BI 7-Day Repo Rate; 2) A unidirectional causality relationship exists between IHSG and inflation; 3) A bidirectional relationship exists between the exchange rate and IHSG.